Analysis of Privacy Protection Mechanism and Information Security Policy as Antecedents of User Trust in E-Commerce Platforms in Indonesia - Agus Purwanto; Joko Santoso; Affan Irfan Fauziawan; I Wayan Karang Utama; Anggun Nugroho (Westscience Press, 2026)
The rapid growth of e-commerce in Indonesia has increased the importance of personal data protection and information security in building consumer confidence. This study analyzes the effects of Privacy Protection Mechanisms and Information Security Policies on User Trust in e-commerce platforms in Indonesia. A quantitative research approach was employed using a cross-sectional survey involving 150 respondents who had experience using e-commerce platforms. Data were collected through a structured questionnaire measured using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 3. The measurement model demonstrated satisfactory reliability and validity. The structural model showed that Privacy Protection Mechanisms had a positive and significant effect on User Trust, while Information Security Policies also had a positive and significant effect on User Trust. The model explained 61.7% of the variance in User Trust, with an R² value of 0.617 and a Q² value of 0.428, indicating satisfactory explanatory and predictive relevance. Information Security Policies emerged as the strongest predictor of User Trust. These findings confirm that both privacy governance and information security management are essential for strengthening consumer confidence in e-commerce platforms. E-commerce providers should therefore improve privacy transparency, user control, authentication, transaction security, fraud prevention, and incident response mechanisms to support sustainable digital trust.